Numerical investigation of the flow in axial water turbines and marine propellers with scale-resolving simulations. (October 2015) - Morgut, Mitja; Jošt, Dragica; Nobile, Enrico; Škerlavaj, Aljaž
Abstract: The accurate prediction of the performances of axial water turbines and naval propellers is a challenging task, of great practical relevance. In this paper a numerical prediction strategy, based on the combination of a trusted CFD solver and a calibrated mass transfer model, is applied to the turbulent flow in axial turbines and around a model scale naval propeller, under non-cavitating and cavitating conditions. Some selected results for axial water turbines and a marine propeller, and in particular the advantages, in terms of accuracy and fidelity, of ScaleResolving Simulations (SRS), like SAS (Scale Adaptive Simulation) and Zonal-LES (ZLES) compared to standard RANS approaches, are presented. Efficiency prediction for a Kaplan and a bulb turbine was significantly improved by use of the SAS SST model in combination with the ZLES in the draft tube. Size of cavitation cavity and sigma break curve for Kaplan turbine were successfully predicted with SAS model in combination with robust high resolution scheme, while for mass transfer the Zwart model with calibrated constants were used. The results obtained for a marine propeller in non-uniform inflow, under cavitating conditions, compare well with available experimental measurements, and proved that a mass transfer model, previously calibrated for RANS (Reynolds Averaged Navier Stokes), can be successfully applied also within the SRS approaches.